Radiation resistant glass and method of making and use thereof

CN122958052APending Publication Date: 2026-10-23CHINA BUILDING MATERIALS ACADEMY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610981657.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

为提高对高剂量(例如伽马辐照剂量大于106Gy,中子或离子辐照剂量大于1 dpa)辐照的耐受性,须掺杂高浓度的二氧化铈,然而,高浓度铈掺杂会导致铈离子的吸收从紫外波段扩展到可见光波段,显著降低玻璃材料的透过率

Benefits of technology

本申请提供了一种玻璃材料,该玻璃材料具有优异的可见光范围内的透光特性与耐高剂量高能射线或高能离子辐照的能力,达成了高光学透过率与强辐照稳定性的协同效应。此外,该材料在化学组成上的配比,保证了其在广泛的环境条件下展现出色的稳定性和加工性能,以便于制造过程中的切割、成型和热处理。因此,本申请的玻璃材料在提供必要的稳定服役效能的同时,不牺牲透光性和加工便利性,并兼具经济性与环境友好性,适用于医疗、工业和研究等复杂或极端辐射环境下安全、可靠和持久耐受高能射线和/或离子的领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958052A_ABST
    Figure CN122958052A_ABST
Patent Text Reader

Abstract

The application relates to a radiation-resistant glass and a preparation method and application thereof. The radiation-resistant glass comprises the following components in percentage by mass: SiO2: 30-75%; B2O3: 5-25%; Na2O: 5-10%; K2O: 5-10%; BaO: 0-25%; CeO2: 2.5-10%; and C: 0.2-2%. The application optimizes the near-ultraviolet and visible light transmittance of the glass by reasonably controlling the adding amount and the ratio of the components, significantly improves the radiation stability, and prepares the radiation-resistant glass with high temperature resistance, high thermal stability and high chemical stability. The radiation-resistant glass can be widely applied to various radiation shielding protection scenes with high requirements for light transmittance and radiation resistance to high-energy rays and / or ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of special glass, and in particular to a radiation-resistant glass, its preparation method, and its application. Background Technology

[0002] High-energy radiation (especially gamma rays) shielding glass materials play an important role in nuclear industry, aerospace, deep space exploration, and radiotherapy. However, strong radiation often causes color centers to form in the visible light region of the glass material, along with changes in refractive index and volume, leading to discoloration, embrittlement, and decreased stability, which greatly restricts its reliability and durability in service.

[0003] Irradiation causes ionization and displacement damage to glass materials. The damage primarily occurs through the transfer of energy carried by high-energy particles or electromagnetic waves via elastic or inelastic collisions. In this process, charged particles and electromagnetic waves mainly cause ionization damage, while high-energy particles primarily cause displacement damage. Typically, the energy threshold required for ionization damage is much lower than that for displacement damage. Therefore, ionization damage caused by irradiation often plays a more significant role in glass. Doping with transition elements or rare earth elements is an ideal and common approach to glass optimization and improvement. Among these, cerium (Ce) doping is particularly effective in improving the radiation resistance of glass. Cerium ions (Ce...) 3+ / Ce 4+ The valence state transition properties of [a specific component] endow it with a unique self-healing ability against radiation damage. It can capture free electrons and holes generated by ionizing radiation through a charge compensation mechanism, thereby suppressing the accumulation of irradiation defects in the glass network structure. To improve its ability to withstand high doses (e.g., gamma irradiation doses greater than 10 [units]), [further action is needed]. 6 To withstand irradiation of Gy (neutron or ion doses greater than 1 dpa), high concentrations of cerium dioxide doping are required. However, high-concentration cerium doping causes cerium ion absorption to extend from the ultraviolet band to the visible light band, significantly reducing the transmittance of the glass material. Under harsh radiation environments, existing glass materials struggle to balance high transmittance and high-dose irradiation resistance.

[0004] Therefore, it is of great significance to provide a glass with high transmittance and resistance to high doses of radiation. Summary of the Invention

[0005] The main objective of this application is to provide a radiation-resistant glass, its preparation method, and its application. The technical problem to be solved is how to provide a radiation-resistant glass that has high transmittance while also having high resistance to high dose radiation, thus making it more suitable for practical use.

[0006] The purpose of this application and the technical problem it solves are achieved by the following technical solution.

[0007] According to this application, a radiation-resistant glass comprises, by weight percentage, the following components: SiO2: 30%~75%; B2O3: 5%~25%; Na2O: 5%~10%; K2O: 5%~10%; BaO: 0%~25%; CeO2: 2.5%~10%; And C: 0.2%~2%.

[0008] The purpose of this application and the technical problems to be solved can also be further achieved by the following technical measures.

[0009] Preferably, the aforementioned radiation-resistant glass further comprises, by mass percentage: NaCl: 0.1%~0.5%.

[0010] Preferably, the aforementioned radiation-resistant glass has a total content of not less than 75% SiO2 and B2O3 by mass percentage.

[0011] Preferably, the aforementioned radiation-resistant glass has a total content of Na2O and K2O of not less than 13% by mass percentage.

[0012] Preferably, in the aforementioned radiation-resistant glass, the ratio of the sum of SiO2 and B2O3 content to the sum of Na2O and K2O content, by mass percentage, is not less than 5.5.

[0013] Preferably, the aforementioned radiation-resistant glass has a coefficient of thermal expansion of (55-65)×10⁻⁶ at 30-300℃. -7 / ℃, glass transition temperature T g ≥650℃, sag temperature T s ≥700℃; The aforementioned radiation-resistant glass, at a thickness of 10 mm, has a maximum transmittance of ≥91.5% and a minimum transmittance of ≥7.5% in the wavelength range of 350-800 nm. The aforementioned radiation-resistant glass, at a thickness of 10 mm, after being irradiated with high-energy rays at a dose of 1E6 Gy and ions at a dose of 1.1 dpa, showed that, compared with before irradiation, the maximum transmittance of the irradiated glass in the wavelength range of 350-800 nm was ≥91%, the minimum transmittance was ≥5.8%, and the transmittance at a wavelength of 550 nm decreased by less than 0.5%.

[0014] The purpose of this application and the solution to its technical problems are also achieved by the following technical solutions.

[0015] The method for preparing any of the aforementioned radiation-resistant glasses according to this application includes the following steps: The glass raw materials are mixed according to the formula to obtain the batch material; The aforementioned batch material is melted at 1450-1600℃, and stirred during the melting process to obtain molten glass; After clarifying the aforementioned molten glass, it is molded using a funnel to obtain the aforementioned radiation-resistant glass.

[0016] The purpose of this application and the technical problems to be solved can also be further achieved by the following technical measures.

[0017] Preferably, in the aforementioned preparation method, the melting time of the batch material is 5-10 hours, and the stirring speed during melting is 5-10 r / min; The molding temperature is 1350-1450℃, and the molding time is 5-10 minutes.

[0018] The purpose of this application and the solution to its technical problems are also achieved by the following technical solutions.

[0019] This application proposes the use of any of the aforementioned radiation-resistant glasses in radiation-resistant shielding devices or radiation-resistant protective windows.

[0020] By employing the above technical solution, the radiation-resistant glass, its preparation method, and its application, as described in this application, have at least the following advantages: This application provides a glass material that exhibits excellent light transmittance in the visible light range and resistance to high-dose, high-energy radiation or high-energy ion irradiation, achieving a synergistic effect of high optical transmittance and strong radiation stability. Furthermore, the chemical composition of this material ensures excellent stability and processability under a wide range of environmental conditions, facilitating cutting, shaping, and heat treatment during manufacturing. Therefore, the glass material of this application provides the necessary stable service performance without sacrificing light transmittance and ease of processing, and is both economical and environmentally friendly, making it suitable for safe, reliable, and durable resistance to high-energy radiation and / or ions in complex or extreme radiation environments such as medical, industrial, and research fields.

[0021] The radiation-resistant glass provided in this application, at a thickness of 10 mm, exhibits a maximum transmittance of ≥91.5% and a minimum transmittance of ≥7.5% in the 350-800 nm wavelength range. After irradiation with high-energy rays at a dose of 1E6 Gy and ions at a dose of 1.1 dpa, the maximum transmittance remains at ≥91% and the minimum transmittance at ≥5.8% in the 350-800 nm wavelength range, with a transmittance decrease of less than 0.5% at 550 nm. This demonstrates that the glass material of this application possesses excellent transmittance in the near-ultraviolet-visible wavelength range, ensuring ease of observation and use within the required range.

[0022] The radiation-resistant glass provided in this application has a coefficient of thermal expansion of (55-65)×10⁻⁶ at temperatures ranging from 30℃ to 300℃. -7 / ℃, glass transition temperature T g ≥650℃, sag temperature T s ≥700℃. It also has good chemical stability, high temperature resistance and mechanical strength, and can be produced in large sizes, making it suitable for various scenarios requiring high light transmittance and resistance to high-energy rays and / or ions for irradiation and / or radiation shielding.

[0023] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, the preferred embodiments of this application are described in detail below with reference to the accompanying drawings. Attached Figure Description

[0024] Figure 1 This is a comparison chart of the transmittance of the radiation-resistant glass in Example 2 (unirradiated) and the glass material in Comparative Example 1 in the range of 350-900 nm. Figure 2 It is via a dose of 1E6Gy 60 Co gamma rays and Si at a dose of 1.1 dpa and an energy of 2.2 MeV. 2+ A comparison of the transmittance of the radiation-resistant glass in Example 2 and the glass material in Comparative Example 1 in the 350-900 nm range after ion-integrated irradiation. Detailed Implementation

[0025] To further illustrate the technical means and effects adopted by this application to achieve its intended purpose, the following, in conjunction with the accompanying drawings and preferred embodiments, provides a detailed description of the specific implementation methods, structures, features, and effects of a radiation-resistant glass, its preparation method, and its application based on this application. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable manner.

[0026] This application discloses a radiation-resistant glass, which, by weight percentage, comprises the following components: SiO2: 30%~75%; B2O3: 5%~25%; Na2O: 5%~10%; K2O: 5%~10%; BaO: 0%~25%; CeO2: 2.5%~10%; And C: 0.2%~2%.

[0027] SiO2 is a glass-forming oxide that can form glass on its own and is the main component of the glass-forming framework. Its structural state within the glass plays a decisive role in its properties. Generally, it forms a silicon-oxygen tetrahedral network within the glass, becoming its framework. A higher silica content can reduce the glass's coefficient of thermal expansion and improve its thermal stability, chemical stability, softening temperature, heat resistance, hardness, and mechanical strength. However, it can also increase the glass's melting point and viscosity during high-temperature melting, making melting more difficult. In this application, the SiO2 content is controlled between 30% and 75%.

[0028] B2O3 is a glass-forming oxide, with boron-oxygen trigonals [BO3] and boron-oxygen tetrahedra [BO4] as its structural units. In borosilicate glasses, it forms a structural network together with silicon-oxygen tetrahedra. B2O3 can reduce the coefficient of thermal expansion of glass, improve its thermal and chemical stability, increase its refractive index, improve its gloss, and enhance its mechanical properties. B2O3 reduces the viscosity of glass at high temperatures and increases it at low temperatures, thus glasses with higher B2O3 content have a wider forming temperature range. B2O3 also acts as a flux, accelerating the melting and refining of glass. However, when the amount of B2O3 added is too high, the coefficient of thermal expansion of the glass actually increases due to the increased number of boron-oxygen trigonals, resulting in a boron anomaly. In this application, the B2O3 content is controlled between 5% and 25%.

[0029] In some embodiments, the sum of the contents of SiO2 and B2O3 is not less than 75%. SiO2 and B2O3 are two network forms in the glass system of this application; SiO2 forms silicon-oxygen tetrahedra, and B2O3 forms boron-oxygen trigonometric or boron-oxygen tetrahedra. A sum of SiO2 and B2O3 content of not less than 75% can further optimize the mechanical strength and chemical stability of the glass.

[0030] Na₂O and K₂O are network oxides in glass. Alkali metal oxides readily migrate and diffuse within the glass matrix, reducing the viscosity of the glass during high-temperature melting and making it easier to melt. They are excellent fluxes, but their introduction should not be excessive, as excessive amounts will increase the coefficient of thermal expansion and reduce the glass's chemical stability, thermal stability, and mechanical strength. In this application, the content of Na₂O is controlled at 5%–10%, and the content of K₂O is controlled at 5%–10%. In some embodiments, the sum of the contents of Na₂O and K₂O is not less than 13%.

[0031] BaO is a divalent network exooxide. It can increase the refractive index, density, luster, and chemical stability of glass, while also improving its ability to shield against high-energy radiation. Small amounts of BaO can accelerate glass melting, but excessive amounts can cause secondary bubbles in the refractory material and severely corrode it. In this application, the BaO content is controlled between 0% and 25%.

[0032] The introduction of CeO2 can help glass maintain color stability under strong radiation, effectively improving its service life. Furthermore, CeO2 decomposes at the melting temperature, releasing oxygen, which can act as a clarifying agent, effectively improving the light transmittance of the glass. However, the amount used must be appropriate; too little will result in an insignificant clarifying effect, while too much can easily cause discoloration and severely reduce the glass's transmittance. In this application, the CeO2 content is controlled between 2.5% and 10%.

[0033] C refers to carbon powder, a black, powdery, carbon-rich material with strong reducing properties. Insufficient carbon powder will not provide the necessary reducing effect. Excessive carbon powder may reduce ferric oxide impurities in the molten glass to ferrous oxide, affecting the optical quality of the glass. In this application, the C content is controlled between 0.2% and 2%.

[0034] In this application, by controlling the content of compounds such as SiO2 and B2O3 that affect the thermal expansion coefficient of glass, a glass with a thermal expansion coefficient of (55-65)×10⁻⁶ at 30℃-300℃ was prepared. -7 Radiation-resistant glass at / ℃. By controlling the contents of SiO2, B2O3, Na2O, and K2O, the high-temperature viscosity of the glass is reduced. By controlling the contents of SiO2, B2O3, and BaO, the glass exhibits good chemical stability, high-temperature stability, and mechanical strength. By controlling the contents of CeO2 and C, the glass's resistance to high-dose radiation is significantly improved. By controlling the BaO content, the glass possesses both radiation resistance and a certain degree of high-energy radiation shielding capability.

[0035] In some embodiments, the aforementioned radiation-resistant glass has a coefficient of thermal expansion of (55-65)×10 at 30-300°C. -7 / ℃, glass transition temperature T g ≥650℃, sag temperature T s ≥700℃; the aforementioned radiation-resistant glass, at a thickness of 10mm, has a maximum transmittance of ≥91.5% and a minimum transmittance of ≥7.5% in the 350-800nm ​​wavelength range; after irradiation with high-energy rays at a dose of 1E6 Gy and ions at a dose of 1.1 dpa, the maximum transmittance in the 350-800nm ​​wavelength range is ≥91%, the minimum transmittance is ≥5.8%, and the transmittance decrease at a wavelength of 550nm is less than 0.5%. High-energy rays refer to electromagnetic waves or particle streams with extremely high energy, such as neutron rays, gamma rays, and / or X-rays, which can penetrate matter and cause atomic ionization.

[0036] In some embodiments, the radiation-resistant glass composition further includes, by weight percentage: NaCl: 0.1%~0.5%. NaCl is a clarifying agent. Because the melting temperature of the glass is high during the melting of radiation-resistant glass, NaCl is suitable as a clarifying agent. NaCl vaporizes and volatilizes at high temperatures, promoting glass clarification. However, excessive addition can easily cause glass emulsification. Therefore, preferably, the NaCl content is controlled at 0.1%~0.5%.

[0037] The method for preparing any of the aforementioned radiation-resistant glasses proposed in this application includes the following steps: The glass raw materials are mixed according to the formula to obtain the batch material.

[0038] The aforementioned batch material is melted at 1450-1600℃, with stirring during the melting process to obtain molten glass. Mechanical stirring can accelerate the homogenization process of the molten glass. Stirring can continuously divide the uneven areas and coarse streaks in the molten glass into very fine and short streaks, increasing the contact surface and facilitating mutual dissolution and diffusion between the molten glass and the streaks, thereby causing the streaks to gradually disappear or decrease.

[0039] After the aforementioned molten glass is clarified at high temperature, it is then molded using a funnel to obtain the aforementioned radiation-resistant glass.

[0040] In some embodiments, the melting time of the aforementioned batching material is 5-10 hours, the stirring speed during melting is 5-10 r / min, the molding temperature is 1350-1450℃, and the molding time is 5-10 minutes.

[0041] This application proposes the application of any of the aforementioned radiation-resistant glasses in radiation-resistant shielding devices or radiation-resistant protective windows. The radiation-resistant glass of this application combines excellent optical transmittance with strong radiation resistance, making it particularly suitable for manufacturing various shielding devices or protective windows operating in high-energy ray and / or high-energy ion irradiation environments. Specifically, this glass can be used as a radiation-resistant glass component for observation windows in nuclear industry hot chambers, protective windows in nuclear fuel reprocessing plants, shielding windows for radioactive medical equipment, radiation protection covers inside spacecraft cabins, protective covers for optical sensors used in deep space exploration, and beam monitoring windows in high-energy physics experimental devices. In the above application scenarios, this glass can effectively withstand penetrating gamma rays, neutrons, and ion irradiation, and its high transmittance characteristics ensure the clarity and accuracy of optical observation, signal acquisition, or visual monitoring. Furthermore, this glass also possesses excellent thermal and chemical stability, enabling long-term service in complex and extreme environments without transmittance attenuation due to irradiation coloration or cracking failure due to thermal stress, thereby significantly improving the service reliability and lifespan of related devices or equipment.

[0042] The present application will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application are still within the scope of protection of the present application.

[0043] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by one of ordinary skill in the art to which this application pertains. Example 1

[0044] This embodiment provides a radiation-resistant glass and its preparation method.

[0045] The preparation method of radiation-resistant glass is as follows: glass raw materials are mixed according to the proportions in Table 1 to obtain a batch.

[0046] The batch was melted at 1450℃ for 5 hours, and mechanical stirring was carried out during the melting process at a stirring rate of 10 r / min to obtain glass melt.

[0047] After clarifying the aforementioned molten glass, it is molded at 1350°C for 10 minutes to obtain radiation-resistant glass.

[0048] Radiation-resistant glass was made into 10 mm thick samples, and its physical properties were tested. The results are shown in Table 1.

[0049] The test methods are as follows: (1) Optical transmittance test: The ultraviolet-visible-infrared spectrophotometer was used for the test. The test wavelength range was 350-800nm. The maximum and minimum transmittance of the sample in the wavelength range of 350-800nm, as well as the transmittance T550 at 550nm wavelength were recorded.

[0050] (2) Radiation resistance test: conducted by Zhengzhou Hongyuan Bioengineering Co., Ltd. 60 Co gamma-ray irradiation, with a total dose of 1E6 Gy and a dose rate of 520 Gy / min; Si was conducted by Beijing Normal University. 2+ Ion irradiation was performed at a dose of 1.1 dpa, an energy of 2.2 MeV, and a fluence of 3.0 × 10⁻⁶. 15 ions / cm 2 After the samples were subjected to the above comprehensive irradiation, their optical transmittance at wavelengths of 350-800 nm was tested again, and the decrease in transmittance at wavelength of 550 nm before and after irradiation was calculated.

[0051] (3) Coefficient of thermal expansion α 30-300℃ Glass transition temperature Tg and sag temperature T s Test: The test was conducted according to the national standard GB / T7962.16-2010. The glass sample was ground and polished into a cylindrical glass strip with a diameter of 6×50mm, and both ends were made parallel. A Netzsch DIL 402 coefficient of thermal expansion tester was used for the test. The heating rate was 5℃ / min, and the data acquisition period was 20ms. The relationship curve between temperature and linear expansion was recorded, and the glass transition temperature T was obtained using the tangent method. g and relaxation temperature T s .

[0052] (4) Acid resistance stability test: The test was conducted in accordance with the national standard GB / T 7962.14-2010. After the surface of the polished glass sample was eroded by the test medium with an acidity of pH 2.9, pH 4.6 and pH 6.0, the time it took for the glass surface to show purple-blue interference color, or to show discoloration or peeling under an incandescent lamp was observed. The acid resistance stability of the glass was graded according to the time.

[0053] (5) Moisture resistance stability test: The test was conducted in accordance with the national standard GB / T 7962.15-2010. The turbidity H0 and H1 of the tested sample and the standard sample (BaK7 glass and ZK9 glass) were measured before and after erosion, respectively. The turbidity value H = H1 - H0 was calculated. The moisture resistance stability level of the glass was obtained by referring to the table based on the comparison with the turbidity value of the standard sample. Example 2

[0054] The difference between this embodiment and Embodiment 1 is that the formulation of the batch material in this embodiment is shown in Table 1, the melting temperature of the batch material is 1600℃, the melting time is 10h, and the mechanical stirring rate is 5r / min; the forming temperature of the glass melt is 1450℃, and the forming time is 5min; other preparation steps, parameters, and testing procedures are the same as in Embodiment 1. The mass percentage of each component and its physical properties of the radiation-resistant glass in this embodiment are shown in Table 1. Example 3

[0055] The difference between this embodiment and Embodiment 1 is that the formulation of the batch material in this embodiment is shown in Table 1, the melting temperature of the batch material is 1550℃, the melting time is 6h, and the mechanical stirring rate is 6r / min; the forming temperature of the glass melt is 1400℃, and the forming time is 8min; other preparation steps, parameters, and testing procedures are the same as in Embodiment 1. The mass percentage of each component and its physical properties of the radiation-resistant glass in this embodiment are shown in Table 1. Example 4

[0056] The difference between this embodiment and Embodiment 1 is that the formulation of the batch material in this embodiment is shown in Table 1, the melting temperature of the batch material is 1480℃, the melting time is 7h, and the mechanical stirring rate is 8r / min; the forming temperature of the glass melt is 1430℃, and the forming time is 6min; other preparation steps, parameters, and testing procedures are the same as in Embodiment 1. The mass percentage of each component and its physical properties of the radiation-resistant glass in this embodiment are shown in Table 1. Example 5

[0057] The difference between this embodiment and Embodiment 1 is that the formulation of the batch material in this embodiment is shown in Table 1, the melting temperature of the batch material is 1570℃, the melting time is 5h, and the mechanical stirring rate is 5r / min; the forming temperature of the glass melt is 1420℃, and the forming time is 10min; other preparation steps, parameters, and testing procedures are the same as in Embodiment 1. The mass percentage of each component and its physical properties of the radiation-resistant glass in this embodiment are shown in Table 1. Example 6

[0058] The difference between this embodiment and Embodiment 1 is that the formulation of the batch material in this embodiment is shown in Table 1, the melting temperature of the batch material is 1530℃, the melting time is 8 hours, and the mechanical stirring rate is 7 r / min; the forming temperature of the glass melt is 1380℃, and the forming time is 7 minutes; other preparation steps, parameters, and testing procedures are the same as in Embodiment 1. The mass percentage of each component and its physical properties of the radiation-resistant glass in this embodiment are shown in Table 1.

[0059] Comparative Examples 1-5 In Comparative Examples 1-5, the weight percentage of each component in the glass material is shown in Table 1. The preparation steps, parameters, and testing procedures of the glass material were the same as in Example 1. The physical properties of the obtained glass material are shown in Table 1.

[0060] Table 1. Component content and physical properties of radiation-resistant glass in Examples 1-6 and shielding glass in Comparative Examples 1-5 of this application.

[0061] Figure 1 This is a comparison chart of the transmittance of the radiation-resistant glass in Example 2 (unirradiated) and the glass material in Comparative Example 1 in the range of 350-900 nm. Figure 2 It is via a dose of 1E6Gy 60 Co gamma rays and Si at a dose of 1.1 dpa and an energy of 2.2 MeV. 2+ A comparison of the transmittance of the radiation-resistant glass in Example 2 and the glass material in Comparative Example 1 in the 350-900 nm range after ion-integrated irradiation.

[0062] As shown in Table 1, the test results in Examples 1-6, by reasonably controlling the amount and ratio of each component, ensured excellent near-ultraviolet and visible light transmittance while also exhibiting outstanding radiation stability. Specifically, the radiation-resistant glass prepared in Examples 1-6 of this application, at a thickness of 10 mm, has a maximum transmittance ≥91.5% and a minimum transmittance ≥7.5% in the wavelength range of 350-800 nm; after a dose of 1E6 Gy... 60 Co gamma rays and Si at a dose of 1.1 dpa and an energy of 2.2 MeV. 2+ After ion irradiation, the maximum transmittance in the wavelength range of 350-800nm ​​is ≥91.4%, the minimum transmittance is ≥5.8%, and the decrease in transmittance (T550) at 550nm wavelength is less than 2%. The overall performance is better than that of the glass materials in Comparative Examples 1-5.

[0063] In summary, the radiation-resistant glasses provided in Examples 1-6 of this application exhibit excellent near-ultraviolet and visible light transmittance and outstanding radiation stability, while also possessing good chemical stability, high-temperature resistance, and mechanical strength. These effects are achieved by introducing a specific ratio of SiO2 and B2O3 as network formations into the glass composition, combining appropriate amounts of Na2O and K2O to optimize melting performance, and adding a key regulating component C to precisely adjust the redox atmosphere of the glass melt, thereby forming Ce. 3+ / Ce 4+ The optimized valence state balance, combined with appropriate melting temperature, forming temperature, and mechanical stirring process, further ensures the optical uniformity and structural density of the glass. Therefore, the radiation-resistant glass of this application has excellent near-ultraviolet and visible light transmittance and excellent radiation stability, and can be widely used in various radiation shielding or protection scenarios where high transmittance and radiation resistance are required.

[0064] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A radiation-resistant glass, characterized in that, It comprises the following components by weight percentage: SiO2: 30%~75%; B2O3: 5%~25%; Na2O: 5%~10%; K2O: 5%~10%; BaO: 0%~25%; CeO2: 2.5%~10%; And C: 0.2%~2%.

2. The radiation-resistant glass according to claim 1, characterized in that, By mass percentage, its components also include: NaCl: 0.1%~0.5%.

3. The radiation-resistant glass according to claim 1, characterized in that, The total content of SiO2 and B2O3 by mass percentage shall not be less than 75%.

4. The radiation-resistant glass according to claim 1, characterized in that, The sum of the contents of Na2O and K2O by mass percentage shall not be less than 13%.

5. The radiation-resistant glass according to claim 1, characterized in that, The ratio of the sum of SiO2 and B2O3 content to the sum of Na2O and K2O content, by mass percentage, is not less than 5.

5.

6. The radiation-resistant glass according to claim 1, characterized in that, The ratio of CeO2 to C content is not less than 5.

0.

7. The radiation-resistant glass according to claim 1, characterized in that, The radiation-resistant glass has a coefficient of thermal expansion of (55-65)×10 at 30-300℃. -7 / ℃, glass transition temperature T g ≥650℃, sag temperature T s ≥700℃; The radiation-resistant glass, at a thickness of 10 mm, has a maximum transmittance of ≥91.5% and a minimum transmittance of ≥7.5% in the wavelength range of 350-800 nm. After being irradiated with high-energy rays at a dose of 1E6 Gy and ions at a dose of 1.1 dpa at a thickness of 10 mm, the irradiated glass exhibits a maximum transmittance of ≥91% and a minimum transmittance of ≥5.8% in the wavelength range of 350-800 nm, compared to before irradiation. Furthermore, the transmittance decrease at a wavelength of 550 nm is less than 0.5%.

8. The method for preparing radiation-resistant glass according to any one of claims 1-7, characterized in that, It includes the following steps: The glass raw materials are mixed according to the formula to obtain the batch material; The batch material is melted at 1450-1600℃, and stirred during the melting process to obtain molten glass; After clarifying the molten glass, it is molded using a perforation process to obtain the radiation-resistant glass.

9. The preparation method according to claim 8, characterized in that, The melting time of the batch is 5-10 hours, and the stirring speed during melting is 5-10 r / min; The molding temperature is 1350-1450℃, and the molding time is 5-10 minutes.

10. The use of the radiation-resistant glass according to any one of claims 1-7 in radiation-resistant shielding devices or radiation-resistant protective windows.